(untitled) (Bangladesh Journal of Otorhinolaryngology, 2026)
Introduction: Parotid gland tumors are a diverse group of salivary gland neoplasms with varying clinical, histopathological, and therapeutic outcomes. They represent the most common site for salivary gland tumors, encompassing both benign and malignant types.This study aimed to assess the clinicopathological patterns and treatment outcomes of parotid gland tumors. Methods: This was a prospective study conducted at the Department of Otolaryngology- Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, on the clinicopathological patterns, treatment outcomes, and complications of parotid gland tumors. A total of 114 patients diagnosed with parotid gland tumors and treated from January 2021 to December 2023 were included. Statistical Package for Social Sciences (SPSS) version 22.0. Result: The highest incidence in the 21–40 age group (35.08%) and a slight female predominance (M:F ratio 1:1.1). Benign tumors accounted for 59 % of cases, with pleomorphic adenoma being most common (45.5%), while malignant tumors comprised 40.9%, led by mucoepidermoid carcinoma (18.2%). Painless swelling was the most frequent clinical feature (63.6%), predominantly seen in benign tumors, whereas malignancies often presented with painful swelling (25.5%), facial nerve weakness (4.6%), and skin fixation or lymphadenopathy. Surgical resection alone had a 77.3% success rate. Common complications included seroma (16.4%) and facial nerve injury (15.5%), with recurrence noted only in malignant cases (5.5%). Conclusion: Surgical resection in benign tumours and surgical resection combined with adjuvant therapy in malignant parotid tumours provided favourable outcome, although complications such as facial nerve injury and seroma were noted. These findings underline the importance of early diagnosis, appropriate surgical intervention, and the role of adjuvant therapies in managing malignant parotid tumors. Bangladesh J Otorhinolaryngol 2025; 31(2): 69-76